‘Poor Protestant Flies’: Conversions to Catholicism in Early Eighteenth Century England - Duffy, Eamon (Studies in church history, 1978)
Through the stormy and divided history of religion in seventeenth and early eighteenth-century England runs one constant and unvarying stream—hatred and fear of popery. That ‘gross and cruel superstition’ haunted the protestant imagination. The murderous paranoia of the popish plot was the last occasion on which catholic blood was spilled in the service of the national obsession, but the need to preserve ‘our Country from Papal Tyranny; our Laws, our Estates, our Liberties from Papal Invasion; our Lives from Papal Persecution; and our Souls from Papal Superstition . . .’ continued to exercise men of every shade of churchmanship, and of none. Throughout the early eighteenth century zealous churchmen sought to keep alive ‘the Spirit of Aversion to Popery whereby the Protestant Religion hath been chiefly supported among us’, and publications poured from the press reminding men of the barbarities of the papists, ancient and modern, the fires of Smithfield and the headman’s axe of Thorn. Catholicism was bloody, tyrannical, enslaving, and cant phrases rolled pat from tongue and pen—popery and arbitrary government, popery and wooden shoes. The tradition was universal, as integral a part of the nation’s self-awareness as beer and roast-beef, and equally above reason. There were, observed Daniel Defoe, ‘ten thousand stout fellows that would spend the last drop of their blood against Popery that do not know whether it be a man or a horse’.